Religions and trade : religious formation, transformation, and cross-cultural exchange between East and West - Wick, Peter. (Dynamics in the History of Religions, 2013)
In Religions and Trade a number of international scholars investigate the ways in which eastern and western religions were formed and transformed from the perspective of "trade." Trade changes religions. Religions expand through the help of trade infrastructures, and religions extend and enrich the trade relations with cultural and religious "commodities" which they contribute to the "market place" of human culture and religion. This leads to the inclusion, demarcation and densification as well as the amalgamation of religious traditions. In an attempt to find new pathways into the world of religious dynamics, this collection of essays focuses on four elements or "commodities" of religious interchange: topologies of religious space, religious symbol systems, religious knowledge, and religious-ethical ways of life.